2017
DOI: 10.1016/j.tranon.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Circular RNAs in Glioblastoma Multiforme and Its Correlation with Prognosis

Abstract: OBJECTIVE: The present study aimed to explore the expression profiles of circular RNAs (circRNAs) in glioblastoma multiforme (GBM) in an attempt to identify potential core genes in the pathogenesis of this tumor. METHODS: Differentially expressed circRNAs were screened between tumor tissues from five GBM patients and five normal brain samples using Illumina Hiseq. Bioinformatics analysis was used to analyze their potential function. CircBRAF was further detected in different WHO grades glioma tissues and norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 32 publications
5
72
0
2
Order By: Relevance
“…The GSE63319 dataset included miRNA microarray data of 11 GBM tissues and four epileptic tissues and was based on GPL16384 Affymetrix Multispecies miRNA‐3 Array (Affymetrix, Inc, Santa Clara, CA) 8 . The GSE103227 dataset, which comprised gene expression microarray data and lncRNA microarray data, was based on GPL16956 Platforms (Agilent‐045997 Arraystar human lncRNA microarray V3 (Probe Name Version), Arraystar Inc, Rockville, MD) and included data from five GBM and five normal brain tissues 9 . The RNA‐seq data expression profiles of GBM were obtained from The Cancer Genome Atlas (TCGA) public database (http://cancergenome.nih.gov/) (as of December, 2018) using the Data Transfer Tool, which included data of 169 GBM and five non‐tumoral brain samples, for DEmRNA and DElncRNA analysis, and the clinical information of the cases was also collected.…”
Section: Experimental Methods and Designmentioning
confidence: 99%
“…The GSE63319 dataset included miRNA microarray data of 11 GBM tissues and four epileptic tissues and was based on GPL16384 Affymetrix Multispecies miRNA‐3 Array (Affymetrix, Inc, Santa Clara, CA) 8 . The GSE103227 dataset, which comprised gene expression microarray data and lncRNA microarray data, was based on GPL16956 Platforms (Agilent‐045997 Arraystar human lncRNA microarray V3 (Probe Name Version), Arraystar Inc, Rockville, MD) and included data from five GBM and five normal brain tissues 9 . The RNA‐seq data expression profiles of GBM were obtained from The Cancer Genome Atlas (TCGA) public database (http://cancergenome.nih.gov/) (as of December, 2018) using the Data Transfer Tool, which included data of 169 GBM and five non‐tumoral brain samples, for DEmRNA and DElncRNA analysis, and the clinical information of the cases was also collected.…”
Section: Experimental Methods and Designmentioning
confidence: 99%
“…CircRNAs are aberrantly expressed in several types of cancer, where they regulate multiple biological processes [115], including in brain tumors [116][117][118] (Table 2). For instance, circSMARCA5 was identified as one of the circRNAs most differentially expressed in a cohort of fifty-six GBM patient biopsies.…”
Section: Back Splicing In Brain Tumorsmentioning
confidence: 99%
“…With advances in high‐throughput sequencing and bioinformatic analysis, accumulated evidence indicated that circRNAs were abundant in mammalian cells and even highly expressed compared with the linear RNA isoforms of the host genes . Recent evidence indicated that the aberrant expression profile of circRNAs occurs in colorectal cancer, bladder carcinoma, breast cancer, and glioblastoma . Therefore, circRNAs are important in the tumorigenesis of various kinds of cancers.…”
Section: Introductionmentioning
confidence: 99%